THE AFFECT OF PERSONAL CHARACTERISTICS, MOTIVATION AND WORK DISCIPLINE AGAINST EMPLOYEE PERFORMANCE - Santi Maodia Fathonah; Kasmir Kasmir (Dinasti International Journal of Education Management And Social Science, 2021)
This research aims to investigate further regarding those influence which come from personal characteristics, motivation and work discipline towards employee performance at PT Hi-Lex Cirebon. The research population was employees from PT Hi-Lex Cirebon, with a total sample of 103 employees. The research method used a quantitative method. The data were processed through Structural Equation Model-Partial Least Square (SEM-PLS) analysis by SmartPLS 3.2.7 software. The results showed that the personal characteristics had a positive influence on employee performance, motivation had none relate to employee performance and work discipline had a positive influence on employee performance.